Efektivitas Program Layanan Samsat Keliling dalam Meningkatkan Kepatuhan Wajib Pajak Kendaraan Bermotor: Studi UPT Samsat Kota Kupang - Francesco Aldy Rota Silli Bataona; Marthina Raga Lay; Rouwland Alberto Benyamin; Made Ngurah Demi Andayana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effectiveness of the Samsat Keliling service program in increasing motor vehicle tax compliance in Kupang City. The approach used is qualitative with a case study method at the Samsat UPT in Kupang City. Data collection techniques include observation, in-depth interviews, and documentation, with data analysis using the Miles and Huberman model. The results show that the program is quite effective based on several indicators, such as targeting accuracy, program socialization, and the achievement of set goals. The Samsat Keliling service has improved public accessibility due to its strategic location placements, although its coverage is not yet fully even due to limited fleets. Program socialization is carried out using various media, but there are gaps in public understanding of the program. The program has also succeeded in increasing tax revenue from IDR 136.8 billion in 2023 to IDR 157.2 billion in 2024 and reducing motor vehicle tax arrears. However, tax compliance is still influenced by individual awareness and the economic condition of the community, which poses a challenge in achieving optimal compliance levels.